2018
DOI: 10.1159/000495960
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Spontaneous Brain Activity and Functional Connectivity in Type 1 Diabetic Patients Without Microvascular Complications

Abstract: Background/Aims: Type 1 diabetes mellitus (T1DM) has been proven to be associated with an increased risk of cognitive dysfunction. In this study, we aimed to investigate whether disrupted spontaneous activity and functional connectivity (FC) exist in T1DM patients using resting-state functional magnetic resonance imaging (rs-fMRI) and to detect the relationships of these parameters with cognitive impairment. Methods: T1DM patients (n=35) were compared with age-, sex-, and education level-matched healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…As previous reported, T1DM impaired cognitive function such as learning and memory in children (32)(33)(34). Compared with the healthy controls, T1DM patients showed significantly reduced FC between the PCC and the right middle frontal gyrus (12). In line with the previous study, our study also showed decreased FC of the PCC in children with new-onset T1DM, indicated that the functions of this brain region were diminished even at the initial stage of T1DM.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As previous reported, T1DM impaired cognitive function such as learning and memory in children (32)(33)(34). Compared with the healthy controls, T1DM patients showed significantly reduced FC between the PCC and the right middle frontal gyrus (12). In line with the previous study, our study also showed decreased FC of the PCC in children with new-onset T1DM, indicated that the functions of this brain region were diminished even at the initial stage of T1DM.…”
Section: Discussionsupporting
confidence: 92%
“…Previous rs-fMRI studies mainly focused on adult T1DM patients. Xia et al found that decreased functional connectivity (FC) was mainly in the default mode network, which was correlated with specific impaired cognition in T1DM (12). In the study done by van Duinkerken et al, T1DM patients showed changes in FC of the subgenual cingulate cortex, mainly manifested as decreased connectivity in executive control network and increased connectivity in default mode network (13).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, fALFF produces better effects in reducing the physiological noise than ALFF, and it can effectively suppress artifacts in non-specific brain regions, such as the ventricles and the vicinity of blood vessels ( Zou et al, 2008 ). ReHo is a data-driven measure for the local measurement of spontaneous neural activity ( Xia et al, 2018 ), and it can effectively evaluate resting-state brain activity based on the hypothesis that brain activity is more likely to occur in clusters rather than in a single voxel ( Zhang et al, 2012 ). Recently, these methods have wide access to explore brain diseases with potential functional alterations, such as depression ( Yu Y. et al, 2019 ), Alzheimer’s disease ( Cheng et al, 2019 ), Tourette syndrome ( Liu et al, 2017 ), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Patients performed worse on several cognitive tests; the researchers speculated that this impaired cognitive performance was correlated with decreased activity in the cuneus and lingual gyrus in the occipital lobe. Recent studies by Xia et al [18] indicated that T1DM patients showed significantly decreased ALFF values in the posterior cingulate cortex (PCC) and right inferior frontal gyrus compared with the healthy controls. Furthermore, they found a positive correlation between decreased ALFF values in the PCC and Rey-Osterrieth Complex Figure Test-(CFT-) delay scores in T1DM patients.…”
Section: Introductionmentioning
confidence: 99%